Control of External Tire Spare Parts 7.50-16 Inefficiency Inventory Costs Based on Economic Order Quantity: (Case Study at PT. XYZ - Jakarta) - Pasha, Azam; Madelan, Sugiyono; Badawi Saluy, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study focuses on inventory control of spare parts outside the prohibition 7.50-16 to streamline inventory costs. The method used is Economic Order Quantity with the type of case study design at the company PT. XYZ with the object of research is the supply of Outer Tire Parts 7.50-16. In data collection, the researcher compares the Traditional or Actual Company Method with the Economic Order Quantity Method in 2019 and 2020. The data that has been collected becomes several references in the calculation so that there is a difference between the two methods. The results show that the Economic Order Quantity method can streamline inventory control beyond 7.50-16 at PT. XYZ.